Oleiferoside W from the roots of Camellia oleifera C. Abel, inducing cell cycle arrest and apoptosis in A549 cells. Issue 8 (3rd August 2018) - Wu, Jiang-Ping; Kang, Nai-Xin; Zhang, Mi-Ya; Gao, Hong-Wei; Li, Xiao-Ran; Liu, Yan-Li; Xu, Qiong-Ming; Yang, Shi-Lin
Abstract: Camellia oleifera C . Abel has been widely cultivated in China, and a group of bioactive constituents such as triterpeniod saponin have been isolated from C. oleifera C. Abel . In the current study, a new triterpeniod saponin was isolated from the EtOH extract of the roots of C. oleifera C. Abel, named as oleiferoside W, and the cytotoxic properties of oleiferoside W were evaluated in non-small cell lung cancer A549 cells. At the same time the inducing apoptosis, the depolarization of mitochondrial membrane potential (Δψ), the up-regulation of related pro-apoptotic proteins, such as cleaved-PARP, cleaved-caspase-3, and the down-regulation of anti-apoptotic marker Bcl-2/Bax were measured on oleiferoside W. Furthermore, the function, inducing the generation of reactive oxygen species (ROS) and apoptosis, of oleiferoside W could be reversed by N-acetylcysteine (NAC). In conclusion, our findings showed that oleiferoside W induced apoptosis involving mitochondrial pathway and increasing intracellular ROS production in the A549 cells, suggesting that oleiferoside W may have the possibility to be a useful anticancer agent for therapy in lung cancer. Abstract :